Pengaruh Media Pembelajaran dan Lingkungan Akademis Terhadap Minat Belajar Mahasiswa - Dyah Ayu Puri Palupi; Mardanung Patmo Cahjono (Kelola: Jurnal Manajemen Pendidikan, 2022)
Smartphone has changed the role of the computer. Every assignment has been done using smartphone. Many students depend on this device for everything. This research aimed to find the effect of learning media and academic environment on learning motivation. This a quantitative research and the object is the students of Economic Faculty Universitas Kristen Surakarta. Data is obtained by distributing a set of questionnaires and the hypothesis is analyzed by multiple regression. The conclusion is there is a positive effect between learning media and learning motivation and there is a positive effect between the academic environment and learning motivation. So, it is hoped that lecturers could be more creative in giving a lecture and improving some games in giving a lecture